Research Attitude, Achievement Motivation, and Self-Efficacy Among Post-Graduate Students Specializing in Primary Education - Umeji, Ifeoma Chinyere (Journal of Education and Teacher Training Innovation, 2024)
This study investigates the research attitude, achievement motivation, and self-efficacy concepts among post-graduate students specializing in primary education. The research aims to understand the interplay between these constructs and their implications for academic success and research engagement. A quantitative research design was employed, and data were collected using structured questionnaires from a sample of 62 post-graduate students. Descriptive statistics, and correlation analyses were conducted to examine the relationships between research attitude, achievement motivation, and self-efficacy. Statistical analyses showed non-significant correlations: between research attitude and achievement motivation (Kendall's tau_b = -.048, p = .881; Spearman's rho = -.036, p = .939), achievement motivation and self-efficacy (Kendall's tau_b = -.109, p = .708; Spearman's rho = -.204, p = .629), and research attitude and self-efficacy (Kendall's tau_b = .293, p = .362; Spearman's rho = .360, p = .427) among post-graduate students. The findings contribute to a better understanding of the factors influencing post-graduate students' research experiences and offer insights for academic institutions to enhance support mechanisms for student researchers. The implications of the study underscore the importance of fostering positive research attitudes, strengthening achievement motivation, and enhancing self-efficacy among post-graduate students specializing in primary education. Targeted interventions can optimize academic support and promote professional development in research-intensive environments